Repositórios de recursos educacionais digitais reutilizáveis: um estudo para a Universidade Aberta do Brasil - Silva, Paulo Henrique Asconavieta da (2009)
This paper presents a study of basic features of a repository of reusable digital educational resources, aiming at the optimization of resources in the production held by the public sphere. Is based on elements of the Theory of Activity, by Yrjö Engeström (1987), the theory of Communities of Practice (CoPs) by Etienne Wenger (1998), and models of software development, as Eric Raymond (1999), targeting a production geared to greater democratization of access and reuse of materials, especially in courses in distance education modality, offered by the Universidade Aberta do Brasil (UAB). The studies concerning production and management of reusable digital educational resources repositories were taken into account mainly the research of David Wiley (1999, 2000, 2001, 2002), Stephen Downes (2001, 2002, 2005) and Robby Robson (2004). Conducts a survey of the initiatives of the federal government to free sharing of information and knowledge, and make a comparison, through the literature research, the criteria listed in the work with the features found in the portals of educational digital content supported by the Ministério da Educação (MEC): the Portal Domínio Público, the Portal do Professor, the Banco Internacional de Objetos Educacionais (BIOE) and Rede Interativa Virtual da Educação (RIVED). Indicates possibilities of optimization in the current process of authorship of digital learning materials in courses of the distance education modality offered by the UAB. The features selected in this study may serve as reference for future construction and remodeling of existing repositories. Was performed a bibliographic research of the kind exploratory.